COVID-19 Implications for migrant care workers - Eva Vilà Sánchez; Colleen Boland; Linda Cottone (Quaderns IEE, 2022)
The global pandemic COVID-19 has strained health care systems and social services and caused an overall negative economic and social impact throughout Europe. Migrants en route to or residing in Europe are especially disadvantaged, not only due to border closures, but also because many were already in precarious situations with limited access to social protection mechanisms or systems in the host country. Those migrants responsible for care work, who are largely women, are especially vulnerable, as these types of jobs during COVID-19 means even more exposure to the virus.